2016
DOI: 10.1086/688879
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Pulse Wave Transit Time is Associated with Right Ventricular–Pulmonary Artery Coupling in Pulmonary Arterial Hypertension

Abstract: Pulmonary pulse wave transit time (pPTT), defined as the time for the systolic pressure pulse wave to travel from the pulmonary valve to the pulmonary veins, has been reported to be reduced in pulmonary arterial hypertension (PAH); however, the underlying mechanism of reduced pPTT is unknown. Here, we investigate the hypothesis that abbreviated pPTT in PAH results from impaired right ventricular-pulmonary artery (RV-PA) coupling. We quantified pPTT using pulsed-wave Doppler ultrasound from 10 healthy age-and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 44 publications
(93 reference statements)
1
28
0
1
Order By: Relevance
“…Therefore, pulmonary arterial stiffness, PAP, and PCWP affect the blood flow velocity in the pulmonary artery. It has been shown that pPTT is not only shortened in PAH but also inversely correlated with PVR and DPG . In another study, pPTT was significantly shorter in PHT than without pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, pulmonary arterial stiffness, PAP, and PCWP affect the blood flow velocity in the pulmonary artery. It has been shown that pPTT is not only shortened in PAH but also inversely correlated with PVR and DPG . In another study, pPTT was significantly shorter in PHT than without pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 90%
“…Increase in pulmonary PWV due to increased pulmonary arterial stiffness might cause shortened pPTT in patients with precapillary PHT. An inverse correlation between PVR and pPTT might be an indication of this situation . In addition, in patients with precapillary PHT, PCWP is usually in the normal range though DPG increases as a result of increased diastolic PAP.…”
Section: Discussionmentioning
confidence: 99%
“…PAH patients from the University of Minnesota Pulmonary Hypertension Program [ 43 ] were analyzed. PAH was defined as mean pulmonary arterial pressure (mPAP) >20 mmHg, pulmonary capillary wedge pressure <15 mmHg, and pulmonary vascular resistance (PVR) >3.0 Wood units, with other causes such as left sided heart disease, chronic lung disease, or chronic thromboembolic disease being ruled out using echocardiography, pulmonary function tests, computed tomography imaging, ventilation perfusion imaging, or invasive pulmonary angiogram [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…RV‐PA coupling was defined 2 ways: TAPSE divided by invasively measured mean pulmonary artery pressure (mPAP) and percentage change in RVFW thickness/mPAP as previously described 29, 30, 31, 32, 33…”
Section: Methodsmentioning
confidence: 99%
“…RV-PA coupling was defined 2 ways: TAPSE divided by invasively measured mean pulmonary artery pressure (mPAP) and percentage change in RVFW thickness/mPAP as previously described. [29][30][31][32][33] Treadmill Walk Distance Exercise capacity was tested by measuring maximal distance run on a motorized treadmill (Simplex II Instrument; Columbus Instruments, Columbus, OH). The initial treadmill speed was 10 m/min and increased 5 m/min every 5 minutes for 30 minutes or until the rat fatigued.…”
Section: Right Ventricular-pulmonary Artery Couplingmentioning
confidence: 99%